1998
DOI: 10.1093/ee/27.5.1280
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Assessment of Interactions Between Larval Coleomegilla maculata and Coccinella septempunctata (Coleoptera: Coccinellidae) in Field Cages

Abstract: This experimental field study examined the interactions between larvae of Coccinella septempunctata L., an introduced Palearctic species, and Co/eomegilla maculata (Degeer), a Nearctic species. The interactions were examined in 5.8-m 3 field cages enclosing potatoes infested with Myzus persicae (Sulzer) (Homoptera: Aphididae). Intra-and interspecific interactions were compared by using 4 measurements: developmental time and survival from 1st instar to adult, adult weight for each coccineJlid species, and M. pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 16 publications
3
27
1
Order By: Relevance
“…Obrycki et al (1998a) reached a similar conclusion in field tests for C7 and Coleomegilla maculata (De Geer). Analysis of mean adult body sizes over time provided no indication that indigenous ladybird individuals became smaller (from increased scramble competition during larval stages) following the establishment of C7 in western North America (Evans 2000).…”
Section: Proposed Mechanismssupporting
confidence: 66%
“…Obrycki et al (1998a) reached a similar conclusion in field tests for C7 and Coleomegilla maculata (De Geer). Analysis of mean adult body sizes over time provided no indication that indigenous ladybird individuals became smaller (from increased scramble competition during larval stages) following the establishment of C7 in western North America (Evans 2000).…”
Section: Proposed Mechanismssupporting
confidence: 66%
“…Such different vertical positions may reduce potential interaction; in addition, in the fields the three species exploit a considerable array of different habitats (Angalet et al, 1979;Mareida et al, 1992;LaMana & Miller, 1996;Colunga-Garcia & Gage, 1998;Obrycki et al, 1998). According to our results and also to the fact that C. maculata is mainly encountered in the herbaceous stratum (Coderre & Tourneur, 1986), competition between H. axyridis and C. maculata should be less important than between H. axyridis and C. septempunc tata.…”
Section: Discussionsupporting
confidence: 53%
“…Previous experiments on larvae showed that interactions between C. septempunc tata and Coleomegilla maculata (DeGeer) did not signifi cantly affect the control of Myzus persicae (Sulzer) (Obrycki et al, 1998). However, no such studies have been conducted on adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We documented two possible mechanisms (competition and intraguild predation between coccinellid larvae) that could be involved. Cage studies conducted to determine if these interactions occur in the ®eld have shown that interspeci®c interactions between C. septempunctata and C. maculata larvae did not signi®cantly aect aphid densities (Ormord 1994;Obrycki and Ormord 1998).…”
Section: Discussionmentioning
confidence: 99%